2023
DOI: 10.1177/21925682231161577
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Column Realignment Using an Anterior-To-Psoas Approach: A Radiographic-Anatomic Feasibility Study at L1-L5

Abstract: Study Design Cross-sectional radioanatomic study. Objective To determine the feasibility of performing an anterior column realignment (ACR) using an anterior-to-psoas (ATP) approach at L1-L5. Methods Axial magnetic resonance images (MRI) of the L1-L5 disc levels obtained at a single institution were obtained and analyzed. The feasibility of performing an ACR was assessed using a combination of the size of the left oblique corridor (OC), the psoas morphology using the modified Moro classification, and the anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, in comparison with the original ACR technique using a transpsoas approach, the authors believe that performing an ACR using the ATP approach may be a safer technique when radioanatomically feasible. A prior study by Hirase et al described the radioanatomic feasibility of performing an ACR using an ATP approach at L1–L5 and found that performing this technique was considered high risk (high-rising psoas or no measurable space between the ALL and the great vessels) in 13.0% of patients at the L2–L3 level, 40.7% at the L3–L4 level, and 89.0% at the L4–L5 level ( 8 ). The majority of the patients within our cohort underwent an ACR using an ATP approach were at the L2–L3 or L3–L4 level, largely due to the location of the focal kyphotic deformity and radioanatomic feasibility as presented by Hirase et al ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in comparison with the original ACR technique using a transpsoas approach, the authors believe that performing an ACR using the ATP approach may be a safer technique when radioanatomically feasible. A prior study by Hirase et al described the radioanatomic feasibility of performing an ACR using an ATP approach at L1–L5 and found that performing this technique was considered high risk (high-rising psoas or no measurable space between the ALL and the great vessels) in 13.0% of patients at the L2–L3 level, 40.7% at the L3–L4 level, and 89.0% at the L4–L5 level ( 8 ). The majority of the patients within our cohort underwent an ACR using an ATP approach were at the L2–L3 or L3–L4 level, largely due to the location of the focal kyphotic deformity and radioanatomic feasibility as presented by Hirase et al ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent study demonstrated the radioanatomic feasibility of performing a complete ALL release and ACR using the ATP approach at the L1–L5 levels, to our knowledge, there are no prior studies that evaluates the clinical application of this technique ( 8 ). Thus, the objective of this study was to describe and evaluate the safety of ACR using an ATP approach with complete release of ALL and annulus for correction of focal kyphotic lumbar deformity.…”
Section: Introductionmentioning
confidence: 99%